Benchmarking w gospodarce lokalnej - Brol, Ryszard (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The paper shows the new proposals for benchmarking usage in: social service management, management of local administration, creating proper conditions for functioning enterprises and for future investors by local government. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 225-231